2023
DOI: 10.3389/fpsyg.2022.1066938
|View full text |Cite
|
Sign up to set email alerts
|

The link between self-uncertainty and conspicuous consumption: Tolerance of uncertainty as a moderator

Abstract: This study, based on self-affirmation theory, aims to investigate the impact of self-uncertainty on individual consumption behavior. Self-uncertainty was categorized into moral, cognitive, and interpersonal self-uncertainty, and different types of self-uncertainty were manipulated through four experiments, including a moral dilemma, a recall paradigm, and a picture quiz task written by E-Prime software to examine the effects of different types of self-uncertainty on conspicuous consumption and their possible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Wang and Tian (2022) revealed the deeper connection between face culture (the composite and unified expression of honor, dignity, self-worth, and prestige given by others and felt by the self in social situations) and conspicuous consumption. Wang et al (2022a) showed that moral, cognitive, and interpersonal self-uncertainty contribute to a stronger tendency to engage in conspicuous consumption. People are more likely to shift intention when they perceive social pressure from their surroundings (Liu et al, 2023); therefore, the external environment also greatly affects people's tendency toward conspicuous consumption.…”
Section: Conspicuous Consumptionmentioning
confidence: 99%
“…Wang and Tian (2022) revealed the deeper connection between face culture (the composite and unified expression of honor, dignity, self-worth, and prestige given by others and felt by the self in social situations) and conspicuous consumption. Wang et al (2022a) showed that moral, cognitive, and interpersonal self-uncertainty contribute to a stronger tendency to engage in conspicuous consumption. People are more likely to shift intention when they perceive social pressure from their surroundings (Liu et al, 2023); therefore, the external environment also greatly affects people's tendency toward conspicuous consumption.…”
Section: Conspicuous Consumptionmentioning
confidence: 99%